Global capital flows and the role of macroprudential policy - Karmakar, Sudipto; Lima, Diogo (Journal of Financial Stability, 2023)
Can countercyclical bank capital buffers reduce the negative effects of global liquidity shocks? We use the Lehman Brothers bankruptcy as a natural experiment to document the role of the banking system as a transmission channel of global financial disturbances to the real economy. Using central bank administrative data, our results suggest that in the aftermath of the Lehman collapse the banking channel is responsible for 1.44% of the aggregate drop in investment and 0.58% of the drop in aggregate employment. In order to evaluate the effectiveness of counter-cyclical macroprudential policies, we model an open-economy with a banking sector. We compare the drop in actual GDP during the 2008 financial crisis against the counterfactual GDP had Basel III style counter-cyclical capital buffers (CCyB) been in place. We find that the GDP drop in the counterfactual scenario would have been 6 p.p. lower than in the data. We also demonstrate the beneficial effects of the CCyB in mitigating tail risk (GDP at Risk). We show that, over a 3–5 year horizon, the GDP distribution with an operational CCyB would have a higher mean and a much thinner left tail when compared to an economy without a CCyB.